2020
DOI: 10.3389/fchem.2019.00903
|View full text |Cite
|
Sign up to set email alerts
|

Selective Adsorption and Purification of the Acteoside in Cistanche tubulosa by Molecularly Imprinted Polymers

Abstract: Acteoside (ACT) is the main component of phenylethanoid glycosides in Cistanche tubulosa, and it is extremely desirable for obtaining high purification of ACT by molecularly imprinted polymers (MIPs) from their extracts. In this study, MIPs were designed and synthetized to adsorb selectively the ACT in C. tubulosa. The effects of different functional monomers, cross-linkers, and solvents of MIPs were investigated. MIPs were studied in terms of static adsorption experiments, dynamic adsorption experiments, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The results demonstrate that 4-VP was successfully polymerized into the MIPs. The presence of the template, which formed hydrogen bonds with 4-VP, probably caused a relatively broad peak at 3629 cm −1 compared to the NIP and MIP infrared spectra (after washing) [ 43 ]. Therefore, the results from the FT-IR spectra suggest that the MIPs were properly synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrate that 4-VP was successfully polymerized into the MIPs. The presence of the template, which formed hydrogen bonds with 4-VP, probably caused a relatively broad peak at 3629 cm −1 compared to the NIP and MIP infrared spectra (after washing) [ 43 ]. Therefore, the results from the FT-IR spectra suggest that the MIPs were properly synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated that the active ingredients of C. tubulosa can be better purified using novel adsorption materials (molecularly imprinted polymers, mesoporous carbon, etc.) [11,12]. Presently, scholars are dedicated to the study of the pharmacologically active ingredients and related mechanisms of action of Cistanche through advanced analytical identification techniques, such as ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption phenomena have numerous industrial and environmental applications, such as desalination, cooling, wastewater treatment, gas or heat storage, and air purification (Burhan et al, 2016a , 2017 , 2018a , 2019a , 2020 ; Xie et al, 2018 ; Oh et al, 2019 ; Shahzad et al, 2019a , b ; Zhao et al, 2020 ). Such processes involve distinct interaction of adsorbate molecules over the porous surface of adsorbent material.…”
Section: Introductionmentioning
confidence: 99%